An ancillary genomics system to support the return of pharmacogenomic results. (19th February 2019) - Rasmussen, Luke V; Smith, Maureen E; Almaraz, Federico; Persell, Stephen D; Rasmussen-Torvik, Laura J; Pacheco, Jennifer A; Chisholm, Rex L; Christensen, Carl; Herr, Timothy M; Wehbe, Firas H; Starren, Justin B
Abstract: Existing approaches to managing genetic and genomic test results from external laboratories typically include filing of text reports within the electronic health record, making them unavailable in many cases for clinical decision support. Even when structured computable results are available, the lack of adopted standards requires considerations for processing the results into actionable knowledge, in addition to storage and management of the data. Here, we describe the design and implementation of an ancillary genomics system used to receive and process heterogeneous results from external laboratories, which returns a descriptive phenotype to the electronic health record in support of pharmacogenetic clinical decision support.